Association of Obstructive Sleep Apnea Syndrome with Leptin Receptor Gene Q223R and K109R Single Nucleotide Polymorphisms in the Iranian Kurdish Population - Alizadeh Severi, Ali; Rasouli, Sharareh; Abdolsamadi, Mohammad; Safari, Fatemeh; Salari, Farhad; Mahdieh, Nejat; Veisi, Kamal; Akbari, Bahman (Genetic testing and molecular biomarkers, 2025)
Obstructive sleep apnea syndrome (OSAS) is a kind of sleep disturbance in which breathing is reduced or stopped for a short time and, if left untreated, can lead to long-term dangerous complications such as heart attack and obesity. Previous studies have shown that leptin receptor (LEPR) gene polymorphisms correlate with obesity and OSAS. This study aimed to measure the correlation of LEPR K109R and Q223R gene polymorphisms with OSAS in the Kurd population of Kermanshah, Iran. This study's population includes 100 patients with OSAS and 100 healthy individuals. Polysomnography diagnostic tests were performed on both patient and control groups. Polymerase chain reaction-restriction fragment length polymorphism was used to check the association between OSAS and LEPR gene polymorphisms. Significant differences were observed in the allelic frequencies and genotype distributions of the LEPR K109R single nucleotide polymorphism (SNP) between the patients with OSAS and those of the healthy controls, whereas no such differences were found in the allelic and genotype frequencies of LEPR gene Q223R polymorphism. Additionally, the genotypic distribution of patients did not correspond to the severity of the disease. The results indicate an association between K109R and OSAS, with no such relation between Q223R and OSAS. Neither of the SNPs showed a link with the disease severity level.